EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN EMPATI SISWA - Ruri Mulinda; evi afiati; Putri Dian Dia Conia (Universitas Sultan Ageng Tirtayasa, 2020)
Character education is a central issue for the education process that is carried out at all levels of education. One result of character education is empathy. Based on the results of ITP and observations of research conducted in class VII of SMP Negeri 7 Serang in 2019/2020, those were all students who had low empathy. The purpose of this research is to study group guidance with sociodrama techniques to increase empathy. This study used a pre-experimental research technique with one group pre-test post-test design. Data collection methods used an empathy questionnaire. The research subjects consisted of 8 students who had low empathy. The results showed that the empathy profile of students obtained a percentage of low category 4%, medium category 81% and high category 15%. While the average in the pre-test was 44.25, while the post-test was 72.12. Based on the results of the average pre-test and post-test there is a difference of an average of 27.87 which provides group guidance with effective sociodrama techniques to improve the class of students in SMP Negeri 7 Serang City 2019/2020. Keywords: Education, Empathy, Sociodrama